A Method of Projecting of Electric Drive for the Traction Vehicle with wn Asynchronous Motor - Bernard Bednarik; Milan Pospisil; Jiri Drabek; Jan Valuska (Communications - Scientific letters of the University of Zilina, 1999)
This contribution describes a computing method of the continuous rating for the traction vehicle with induction traction motors. A method of specifying probable mechanical and electrical parameters and characteristics of the asynchronous motor as well as relationships and methods for calculation of probable traction characteristics of the vehicle will be shown.